Market Anomalies and Investor Behavior: The January Effect in ASEAN Countries - Mubaroq, Afiq Chamim; Styorini, Christina Tri; Rafinda, Ascaryan; Ramdhani, Pangeran Fajar; Alhendi, Osama; Ikhsanudin, Muhammad Arif (ETIKONOMI, 2025)
Research Originality: This study provides a fresh contribution to the literature on market anomalies, specifically the January Effect, within ASEAN capital markets. Research Objectives: The objective of this research is to investigate the presence and extent of the January Effect by analyzing stock returns and abnormal returns of publicly listed companies in ASEAN capital markets. Research Methods: Data were obtained through purposive sampling, resulting in a final sample of 153 companies. The research hypotheses were tested using paired sample t-tests. Empirical Results: The findings indicate that the January Effect is evident in certain capital market indices within ASEAN but is not consistently observed across all markets. The presence of higher stock returns and abnormal returns in January does not conclusively confirm the January Effect in every instance. Implications: Investors are advised to exercise caution and not rely solely on seasonal anomalies, a comprehensive approach that includes broader market fundamentals and macroeconomic indicators is essential for sound decision-making within ASEAN capital markets. JEL Classification: E22, F21, G14